PENGARUH PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS BUNGA (Brassica oleracea Var. Bathytis L.) PADA OXIC DYSTRUDEPTS LEMBANTONGOA - Mustika Sari, Anshar Pasigai, Imam Wahyudi, Kurnia (AGROTEKBIS, 2016)
Cabbage flowers a vegetable that comes from sub tropical regions. Temperature range for growth of cabbage flowers that minimum and maximum 15.5 to 18 0C 24 0C, so plants can grow cabbage flowers in lowland and highland. Oxic Dystrudepts was characterized by a high level of soil acidity, nutrient and organic matter is low. One way to increase growth and yield of cabbage flowers crop production by performing fertilization. Poultry manure used in this study is chicken manure. This study aimed to study the effect of poultry manure on the growth and yield of cabbage flowers (Brassica oleracea var. Bathytis L. ) in Oxic Dystrudepts Lembantongoa. The research was conducted on October 2014 until February 2015, in the Greenhouse of Agriculture Faculty, Tadulako University, Palu. The soil and the plant analysis were carried out in the Laboratory of Soil Science, Agriculture Faculty, Tadulako University, Palu. The soil for research were taken from Lembantongoa village, Palolo district, Sigi Regency, Central Sulawesi. The researcher applied a random block design and used chicken cage fertilizer as a treatment with seven levels of dose, namely: control, 10t ha-1, 15t ha-1, 20t ha-1, 25t ha-1, 30t ha-1, 35t ha-1. The data were analyzed based on the design used and followed by HSD 5% test. Cabbage flowers plant growth (height , number of leaves , leaf area , chlorophyll , fresh weight of flower/crop, and plant dry weight) was significantly affected by the dose of poultry manure.